As an Intervening Variable Trust, the Influence of Functional Value, Social Value, and Emotional Value on Purchase Intention - Gadang Raharja; IBN Udayana; Putri Dwi Cahyani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
Tokopedia is an online retail platform that can be found and downloaded from the Playstore Web. This study examines the functional, social, and emotional effects of Trust on Purchase Intention among Tokopedia users. The study employs quantitative methodology, including gathering, evaluating, and presenting data in numerical rather than narrative form. The sample wore purposive Random Sampling. A total of 102 people were polled from Tokopedia's various user groups. Based on the findings, it is clear that Functional Value has no positive or substantial impact on Trust. Social value has a positive impact on Trust and is related to it. The emotional value has a favorable impact on the Trust and is related to it. Trust has a beneficial impact on purchasing intentions and is related to them. A one-tailed probability of higher than 0.5 indicates that practical value does not affect Purchase Intention as a Trust intervening variable. As a Trust intervening variable, a one-tailed probability smaller than 0.5 suggests that social value affects Purchase Intention. A one-tailed chance of less than 0.5, on the other hand, implies that emotional value influences Purchase Intention as a Trust intervening variable. Functional Value, Social Value, Emotional Value, Purchase Intention, and Trust are used in this study.